Terjebak Bosan, Larut di Layar: Pengaruh Leisure boredom dan Kecanduan Media Sosial terhadap Perilaku Phubbing pada Gen Z di Karawang - Wahidati, Salsabila; Mubina, Nuram; Minarsih, Yulyanti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The rapid development of digital technology has significantly influenced social interaction patterns, particularly among Generation Z, who are characterized as digital natives. One emerging behavioral phenomenon is phubbing, defined as ignoring others during face-to-face interactions due to excessive smartphone use. This study aimed to analyze the influence of leisure boredom and social media addiction on phubbing behavior among Generation Z in Karawang. Leisure boredom refers to a subjective experience arising from a mismatch between available leisure time and the need for meaningful and satisfying activities, while social media addiction denotes excessive and compulsive use of social media that disrupts emotional and social functioning. A quantitative approach with a causal associative design was employed in this study. The participants consisted of 377 Generation Z individuals residing in Karawang, selected using convenience sampling techniques. Data were collected using adapted versions of the Leisure Boredom Scale (LBS), the Social Media Disorder Scale (SMD), and the Generic Scale of Phubbing (GSP). Multiple regression analysis was conducted to examine the effects of the independent variables on phubbing behavior. The results indicated that leisure boredom and social media addiction had a positive and significant influence on phubbing behavior among Generation Z in Karawang, both simultaneously and partially. The model explained 66.7% of the variance in phubbing behavior, suggesting a substantial effect of these psychological factors. These findings imply that individuals who experience higher levels of boredom during leisure time and stronger dependence on social media are more likely to engage in phubbing behavior. This study highlights the importance of managing leisure activities and regulating social media use to reduce maladaptive social behaviors among Generation Z. The results provide practical implications for preventive interventions, psychoeducation, and guidance programs aimed at promoting healthier digital habits and improving the quality of face-to-face social interactions.